(untitled) (Journal of the College of Basic Education, 2022)
As English is heavily idiomatic, this paper attempts to answer the question how Iraqi learners can better understand and speak English when interacting with native speakers of English from hearing and being exposed to constructed dialogue in TV drama. Hence, the paper has two focal points: the linguistic (semantic and syntactic) construction of idioms in dialogue scripted for the screen and the problems that Iraqi learners encounter in learning English idioms and fixed expressions. An idiom is the assigning of a new meaning to a group of words which already have their own meaning. Idioms can be easily identified with the familiar parts of speech. Thus, some idioms are clearly verbal in nature: "figure out/shy away from," an equally large number are nominal in nature: "feet of clay", many are adjectives: "butterflies in my stomach," and many are adverbial: "high and dry." These idioms which correlate with the familiar parts of speech can be called "lexemic idioms." The other most important group of idioms are of larger size. Often they are an entire clause in length: "have the guts," "have the stomach for," "to be caught between the rock and a hard place. As the English of advanced students, while grammatically, phonologically, and lexically correct, may sound rather bookish and pedantic to a native speaker. Iraqi learners have difficulties in understanding idioms for a number of reasons: idioms have figurative unpredictable meaning, distinctive cultural features, they exist in large numbers and thus difficult to memorize, lack of frequent use, and inadequate method of learning idioms. The study shows that learning idioms in the appropriate context of situation will result in learners’ understanding and speaking better and more fluent English. The study hence not only contributes to the fields of linguistic stylistics and media studies, but also to applied linguistics and pragmatics, in particular through revising the concept and meaning of idioms.